2003
DOI: 10.1002/j.1939-4640.2003.tb02693.x
|View full text |Cite
|
Sign up to set email alerts
|

Male Genital Tract Inflammation: The Role of Selected Interleukins in Regulation of Pro‐Oxidant and Antioxidant Enzymatic Substances in Seminal Plasma

Abstract: Human semen contains spermatozoa as well as populations of round nonspermatozoal cells primarily consisting of leukocytes. Activation of white blood cells present in the seminal plasma during genital tract inflammation and cellular reactions against microbial agents may provoke a release of a variety of products such as cytokines and reactive oxygen species. The aim of this study was to evaluate whether a panel of selected cytokines (interleukin [IL]-1␤, IL-6, IL-8, and tumor necrosis factor-␣ [TNF␣]) detectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
92
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 54 publications
13
92
0
3
Order By: Relevance
“…LCS was associated with decreased sperm count, % normal forms and fructose concentration, a measure of seminal vesicle function. Thus, the present study confirms and extends earlier reports that STIs and LCS are associated with poor semen quality (7,13,45,48,49,51,64,65,70,(77)(78)(79)(80)(81)(82).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…LCS was associated with decreased sperm count, % normal forms and fructose concentration, a measure of seminal vesicle function. Thus, the present study confirms and extends earlier reports that STIs and LCS are associated with poor semen quality (7,13,45,48,49,51,64,65,70,(77)(78)(79)(80)(81)(82).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, concentrations of all three inflammation markers (PMNs, PMN-elastase and IL-1β) were significantly correlated with one another, which was expected, as both PMNs and macrophages are important participants in inflammatory responses, and because numbers of PMNs and macrophages in semen are highly correlated (9,45,48,49,86). STI DNA was not associated with elevations in any of these inflammation markers.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The results from the present study indicated that the concentrations of IL-1b and TNF-a in the testes of male mice infected with PRV were increased, which were similar to other studies (Sanocka et al, 2003). Sanocka et al (2003) found that seminal plasma IL-1b concentration from normozoospermic infertile men with genital tract inflammation was significantly higher than that of controls. Other studies have shown that TNF-a concentration in the seminal plasma of patients with bacterial or mycoplasmal infections was higher than in normal controls (Gruschwitz et al, 1996).…”
Section: Discussionsupporting
confidence: 91%
“…TNF-a is another pro-inflammatory cytokine in the initiation and orchestration of the inflammatory response against invading microorganisms (Hales et al, 1999). The results from the present study indicated that the concentrations of IL-1b and TNF-a in the testes of male mice infected with PRV were increased, which were similar to other studies (Sanocka et al, 2003). Sanocka et al (2003) found that seminal plasma IL-1b concentration from normozoospermic infertile men with genital tract inflammation was significantly higher than that of controls.…”
Section: Discussionsupporting
confidence: 89%